180k views
5 votes
What is 6 (5x + 2y) -3 (2x + 3y) ?

User Gerlando
by
5.5k points

2 Answers

1 vote


\text{Hello there!}\\\\\text{Use the distributive property and combine like-terms to get your answer:}\\\\6(5x + 2y) -3 (2x + 3y)\\\\\text{Distribute:}\\\\30x+12y-6x-9y\\\\\text{Combine like terms:}\\\\24x+3y\\\\\boxed{\text{Answer: 24x+3y}}

User Gnaggnoyil
by
5.0k points
4 votes

Answer:

=24x+3y

Explanation:

6(5x+2y)−3(2x+3y)

Distribute:

=(6)(5x)+(6)(2y)+(−3)(2x)+(−3)(3y)

=30x+12y+−6x+−9y

Combine Like Terms:

=30x+12y+−6x+−9y

=(30x+−6x)+(12y+−9y)

=24x+3y

User Fabi
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.